In the radiance of enlightenment: The influence of nontheistic religions on corporate default risk - Feng Y; Hao W; Fang J; Wongchoti U (Elsevier B V, 2024)
We investigate whether religious site density around a firm's headquarters is related to corporate default risk in China. We find that public firms surrounded by a higher number of Buddhist and Taoist temples are associated with lower default risk. In contrast to the widely documented impact of Western religiosity on corporate behavior, our mechanism tests indicate that lower default risk related to religious site density is primarily driven by better corporate governance and not by a surge in corporate conservatism. Finally, we find that this default risk lowering effect is more pronounced when firms also possess greater political resources.
Keywords: Religion; Default risk; Chinese market; Buddhism; Taoism; Political intervention; Corporate governance; Conservatism; Managerial early life experience; Altman's Z-score